Solving Exponential and Logarithmic Equations

megslove1212

New member
Joined
Nov 16, 2010
Messages
4
I need help explaining how to do this type of problem.

log3(x-9)+ log3(x-3)=2

and

3^(x+4)= 6^(2x-5)

Help please! THANKS!
 
megslove1212 said:
I need help explaining how to do this type of problem.

log3(x-9)+ log3(x-3)=2

Log law:

\(\displaystyle log_{3}(x-9)+log_{3}(x-3)=log_{3}((x-9)(x-3))\)

\(\displaystyle log_{3}((x-9)(x-3))=2\)

base rule:

\(\displaystyle (x-9)(x-3)=3^{2}\)

Now, solve the quadratic. Make sure to check both solutions. Only one may be valid.

3^(x+4)= 6^(2x-5)

Help please! THANKS!

\(\displaystyle 3^{x+4}=6^{2x-5}\)

\(\displaystyle 3^{x}\cdot 81=\frac{36^{x}}{7776}\)

\(\displaystyle 3^{x}\cdot 629856=36^{x}\)

\(\displaystyle 629856=12^{x}\)

12 to what power equals 629856?.
 
Top